The benefits of being a senior mentor: Cultivating resilience through the mentorship of health professions students. Issue 3 (3rd July 2017) - Halpin, Sean N.; Dillard, Rebecca L.; Idler, Ellen; Clevenger, Carolyn; Rothschild, Elizabeth; Blanton, Sarah; Wilson, Jessica; Flacker, Jonathan M.
ABSTRACT: Senior Mentor Programs (SMPs) pair community-dwelling older adults with health professions students to facilitate knowledge, improve communication skills, and promote positive attitudes regarding the aging process. Although evidence exists that SMPs meet these goals, the programs' psychosocial impact on the senior mentors remains unexplored. The current study assessed 101 mostly female (64.4%) senior mentors (M age = 77.6) pre- and postprogram. Although mentors had no change in the amount of perceived ageism experienced or expectation of experiencing ageism, their concern/anxiety over ageism significantly decreased from pre- (M = 21.58) to posttest (M = 20.19). Qualitative thematic analysis indicated meaningfulness of program and scheduling difficulties as prevalent themes. Mentors who reported less concern about ageism following the program were more likely to have experienced ageism in the year prior to the program and to attend religious services more often, another potential intergenerational contact. These results highlight possible benefits of mentor service for older adults.